Dari Druzhba ke Mirnoye Sosushyestvovaniye - Fahrurodji, Ahmad (Masyarakat Sejarawan Indonesia, 2017)
The dissertation examines the dynamic of diplomatic relations between the Soviet Union and Indonesia in the period of 1945-1964, which, focus of Soviet perspective, covers the last decade of Stalin’s post-world war II period until the end of Khruschev’s leadership in 1964. This research is a historical research using qualitative methodology. Geopolitical and international relations approach is used in this study to examine role of diplomatic tradition in strenghtening Soviet influence in the Third countries during the last decade of Stalin and the whole of Khruschev periods. The conceptual frameworks druzhba (friendship) and mirnoye sosushyestvovaniye (peaceful coexistence), and spaseniye mira (world salvation) are used to get better understanding of the picture of the period. In the Russian perspective, the value of druzhba (friendship) that containes vernost’ (loyalty) and iskrennost (honesty) shape the basis for Russia’s attitudes, which implemented in different ways in different time. The results of this study indicate the influence of ‘druzhba’ and mirnoye sosushyestvovaniye values, rooted in the tradition of Russian thought, in diplomatic relations between both countries.